Sistem Informasi Perencanaan Pembangunan Desa Pada Kantor Desa Kaligintung (Studi Kasus Kantor Desa Kaligintung) - Raih Wisma Asri; Imam Tri Suryadin (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2020)
Raih Wisma Asri, "Village Development Planning Information System at Kaligintung Village Hall Office". FinalProject DIII Informatics Engineering Program, under the guidance of Imam Tri Suryadin, M.Kom. 89 pages + xxxiii +attachments. In the context of implementing the mandate of Law Number 25 of 2004 concerning the National DevelopmentPlanning System, Law No. 17 of 2003 concerning State finance, a village must have a well-planned plan based onparticipation and transparency and democratization that develops in villages that are summarized in the VillageMedium-Term Development Plan (RPJM-Desa). this is a strategic village development plan within 6 (six) years.However, the recording of development planning data in Kaligintung village still uses a conventional system in a book,then recaps again to make a report. The process has many shortcomings including errors and lack of accuracy and cancause duplicate data. And there are no detailed reports for development planning that are expected to produce acomputerized RPJMD to make it more efficient and effective. In addition, proper budgeting of funds is also needed sothat the funds used will be right on target. Based on the description above, in this study a village development planning information system will be made atthe Kaligintunf village office. The author uses data collection techniques obtained using literature study, interviews, andobservation. The design of the system used is web-based, which can make it easier to add, delete, print planning data,and make reports more effective and efficient as it makes it easier to find data so that it doesn't spend much time. Thepurpose of writing this Final Project Report is to implement the Village Development Planning Information System atthe Kaligintung Village Hall Office.The results of the development of this system are able to provide convenience in processing development planning datathat is in the Kaligintung Village Hall Office.